(untitled) (Applied Biological Research, 2015)
The present study was aimed to elucidate the distribution of various enzymes in sublingual salivary gland of neonatal buffalo (n = 10), ranging from 1 to 3 months age, and correlate these enzyme systems with the secretory activity of gland. At 1 month age, a uniform moderate to strong positive diffused granular alkaline phosphatase activity was observed in serous acini and ductal epithelium. A moderate positive glucose-6-phosphatase and succinic dehydrogenase activity was seen close to the basement membrane. At 2 months age, glutamic dehydro genase showed moderate activity in basal portions of serous acinar cells, while succinic dehydrogenase activity was strong, granular and evenly distributed in basement membrane of serous cells. Weak activity of monoamine oxidase and moderate non-specific esterase activity was seen. At 3 months age, alkaline phosphatase showed strong positive perinuclear activity in acinar cells, while glucose-6-phosphatase showed a moderate to strong activity in acinar cells and in ductal epithelium. Moderate to strong positive non-specific esterase activity was localized in nerve fibres of intralobular and interlobular connective tissues. Glucose-6-phosphate dehydrogenase and nicotinamide adenine dinucleotide diaphorase showed strong positive granular activity in basement membrane of serous acinar cells and ducts. The high basal activities of oxidoreductases were because of basal mitochondria and were associated with high energy production to meet the energy